Reconciliation of Social Movement: Debate of Syarikat Indonesia's Role in the Advocay of the 1965' Victims - Pratama, Dito Alif (The Faculty of Ushuluddin and Humanities, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2023)
The 1965 tragedy that befell the Indonesian Communist Party (PKI) and Nahdlatul Ulama (NU) left deep wounds on Indonesian society. Reconciliation efforts between these two groups still face various challenges, both from the government and from the people. This research aims to examine the Syarikat Indonesia people's movement, which is one of the reconciliation initiatives between the PKI and NU. This research also wants to know the function of the Company as a social movement that seeks to change society. This research uses qualitative methods that integrate text analysis and interviews with Syarikat members and sympathizers. The data collected was then analyzed using a social movement theoretical framework. This research provides a new contribution by revealing the dynamics and obstacles faced by the Company in carrying out reconciliation. This research also shows how the Syarikat provides an alternative narrative about the events of 1965 that differs from the official state narrative. In addition, this research highlights the role and impact of Syarikat in promoting democratization and social justice in Indonesia.